Capitalism and Global Inequality: Core-periphery Relations in the Context of World System Theory - Budhathoki, Drona (International Research Journal of MMC, 2025)
Capitalism is a mode of production based on surplus value accumulation, where capitalists profit by exploiting wage labor and generating structural inequalities globally. Core nations, with industrial and financial dominance, control production and trade, while peripheral nations supply raw materials and cheap labor. This systemic unequal exchange perpetuates class struggle and global economic disparities. The main objective is to examine how global capitalist structures sustain inequalities between core and peripheral regions through the framework of world-systems theory. This study employed a Comparative-historical research design using secondary sources, including scholarly works, The Development of Underdevelopment, and Modern World-System, etc. It examines structural inequalities between core and peripheral nations through themes like surplus value, capital accumulation, and dependency, applying thematic and comparative analysis within world-systems frameworks. This study concludes that world-systems perspectives remain vital for analyzing global capitalism and inequality. Surplus value extraction, capital accumulation, and unequal exchange sustain disparities between core and peripheral nations. Integrating historical, economic, and technological insights, including Nepal’s context, it highlights structural inequality and concludes with guidance for equitable policy, balanced development, and inclusive global transformation. This study highlights the significance of world-systems perspectives in explaining capitalism and global inequality. It illustrates how core–periphery relations generate structural disparities through labor exploitation, uneven trade, and capital accumulation. Such analysis informs policy debates, guiding equitable development, justice, and sustainable global transformation in the 21st century. This study will be useful for those seeking information about the global inequalities created by capitalism in the contemporary world.